PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN DAN FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Non-Keuangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2017) - Yuni Laras Sati; Andrian Budi Prasetyo (Diponegoro Journal of Accounting, 2019)
This study aims to examine empirically the effect of corporate governance on financial performance and financial distress. Agency issues are a concern for corporate governance practices to deal with these problems. Financial performance is measured by Tobin’s Q, while financial distress uses Altman Z-Score. This study uses two models in testing hypotheses. The first model uses multiple regression analysis to test the first hypothesis. The second model uses logistic regression analysis to test the second hypothesis. The results of this study indicate that corporate governance does not affect financial performance, but has a significant negative effect on financial distress.